2014
DOI: 10.4314/njt.v33i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Exergetic Modelling of Oil-Fired Steam Boilers

Abstract: ABSTRACT ABSTRACT T T T The performance variables and potential he performance variables and potential he performance variables and potential he performance variables and potential Operational parameters of steam boilers using low pour fuel oil (LPFO) and diesel were used to Operational parameters of steam boilers using low pour fuel oil (LPFO) and diesel were used to Operational parameters of steam boilers using low pour fuel oil (LPFO) and diesel were used to Operational parameters of steam boilers using low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It follows from their study that; the irreversibility is maximum in the boiler than in the other components of the system. Studies carried out by Ohijeagbon et al [4] on the exergetic modelling of a steam boiler of oil fire shows that the destroyed exergy in the boiler decreased to 14.6% as the evaporation ratio increased from 10 to 14. The authors showed that the major area to control irreversibility resulting from entropy effects is the combustion product entropy which leads to increased exergy destruction in combustion unit.…”
Section: Introductionmentioning
confidence: 99%
“…It follows from their study that; the irreversibility is maximum in the boiler than in the other components of the system. Studies carried out by Ohijeagbon et al [4] on the exergetic modelling of a steam boiler of oil fire shows that the destroyed exergy in the boiler decreased to 14.6% as the evaporation ratio increased from 10 to 14. The authors showed that the major area to control irreversibility resulting from entropy effects is the combustion product entropy which leads to increased exergy destruction in combustion unit.…”
Section: Introductionmentioning
confidence: 99%
“…Exergy losses remain a major challenge in many industrial processes [ 10 ] and cannot be identified with conventional energy analysis. More recently, exergy analysis has been used to analyze manufacturing processes and equipment, including the evaluation of ultra-high-temperature milk pasteurization plants, assessment of the efficiency of industrial food chains, development of a more sustainable chemical industry advancement procedure, ethanol production process analysis, assessment of a burner in cement production processes, analysis of a refrigeration system in a typical beverage manufacturing plant, vegetable oil production process analysis, cryogenic air separation plants, and steam boiler analysis [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 56 , 57 ]. Exergy analysis has been established as a tool commonly used to determine the quality of energy and resource of any system or process.…”
Section: Introductionmentioning
confidence: 99%